KangSayur Application Interface Design Using Design Thinking Method and System Usability Scale - Fadmi Rina; Muhammad Mufti Ardani; Umi Inayatul Hidayah; Miftahur Rohmah (Journal of Information Technology, Computer Engineering and Artificial Intelligence (ITCEA), 2024)
Problems that often occur in buying and selling vegetables include problems related to the quality of vegetables received by consumers, payment methods that still apply traditional models and the unavailability of vegetables among sellers causing inefficient use of time. The existence of the KangSayur application can facilitate ordering vegetables by keeping the quality of vegetables fresh when they arrive at consumers, various payment methods and the availability of vegetables that can be monitored via cellphones. This research aims to apply the design thinking method to the design of the KangSayur application user interface. The final result of this research is the UI/UX design of KangSayur application with user experience analysis using the system usability scale (SUS) testing method to determine the effectiveness of the application in its use. This research process consists of making UI/UX design using figma tools and design thinking method which has several stages including empathize, define, ideate, prototype and test.